Wakefulness of Happiness. Imaginaries to Rethink Education in the Era of Environmental Crisis - Leff, Enrique (2007)
Thinking happiness as the antidote to despair, and revealing its natural impossibility to be apprehended. The conquer and learning of happiness is essential to achieve a new world without oppression among humans, without exclusion of cultures nor knowledge and without environmental degradation.